1986
DOI: 10.1099/0022-1317-67-12-2819
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Infection of Rats with Haemorrhagic Fever with Renal Syndrome Virus and their Antibody Responses

Abstract: SUMMARYNewborn (within 24 h after birth), 1-week-old and 6-week-old (adult) rats were inoculated with a Hantaan-related virus (B-l) and attempts were made to isolate the virus from various organs. Virus-specific antigens were detected in various organs of newborn rats. Moreover virus could be isolated from almost all their organs even 25 weeks after infection. In contrast, in rats infected at 6 weeks of age the virus could be isolated from various organs but its concentration decreased progressively with time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 28 publications
0
25
1
Order By: Relevance
“…or i.p. infection with Hantaan or Seoul viruses 10,[13][14][15][16][17] . In nature, it is likely that infection of newborn rodents only occurs by aerosol exposure or contact with a recently infected dam; the significance of these findings is therefore unclear.…”
Section: Seoul Virusmentioning
confidence: 99%
See 3 more Smart Citations
“…or i.p. infection with Hantaan or Seoul viruses 10,[13][14][15][16][17] . In nature, it is likely that infection of newborn rodents only occurs by aerosol exposure or contact with a recently infected dam; the significance of these findings is therefore unclear.…”
Section: Seoul Virusmentioning
confidence: 99%
“…As was found for Hantaan virus infection of Apodemus, experimentally inoculated and wild-caught Seoul-virus-infected rats excrete virus in urine; however, virus shedding is not consistently observed 20 . Although both naturally and experimentally infected rats have viral antigen in many of their tissues and organs, with lungs generally having the highest antigen concentration 13,20 , the duration of Seoul virus persistence is poorly defined. In separate studies, newborn rats were found to have viral antigen in their organs for at least 25 weeks 13 and adult rats for at least 75 days 20 after infection ( Table 2).…”
Section: Seoul Virusmentioning
confidence: 99%
See 2 more Smart Citations
“…Infection of newborn rodents with hantaviruses was fatal (Tsai et al, 1982;Kurata et al, 1983;Yamanouchi et al, 1984;Kim et al, 1985;Tanishita et al, 1986), but infection of adults with these viruses resulted in prolonged infection without any clinical symptoms Yanagihara et al, 1985a, b). Recently, T cellmediated immunity was suggested to play a crucial role in resistance of mice to HV infection (Nakamura et al, 1985 a, b).…”
Section: Introductionmentioning
confidence: 99%